2015
DOI: 10.1016/j.bbagen.2014.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Prolyl isomerases in gene transcription

Abstract: Background Peptidyl-prolyl isomerases (PPIases) are enzymes that assist in the folding of newly-synthesized proteins and regulate the stability, localization, and activity of mature proteins. They do so by catalyzing reversible (cis-trans) rotation about the peptide bond that precedes proline, inducing conformational changes in target proteins. Scope of Review This review will discuss how PPIases regulate gene transcription by controlling the activity of (1) DNA-binding transcription regulatory proteins, (2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 231 publications
(324 reference statements)
0
56
0
1
Order By: Relevance
“…Proline isomerization has demonstrated roles at each step of transcriptional regulation, from protein folding and regulation of transcription factor interactions, to modification and recognition of histone tails, and conformational control of the RNA Pol II C-terminal domain that controls its activity (reviewed in (Hanes, 2015)). Although we provide evidence in support of a binary conformational switch in the TAD by NMR and its ability to influence circadian timekeeping in cellular reconstitution assays, we still don't understand exactly how the switch regulates circadian period.…”
Section: Discussionmentioning
confidence: 99%
“…Proline isomerization has demonstrated roles at each step of transcriptional regulation, from protein folding and regulation of transcription factor interactions, to modification and recognition of histone tails, and conformational control of the RNA Pol II C-terminal domain that controls its activity (reviewed in (Hanes, 2015)). Although we provide evidence in support of a binary conformational switch in the TAD by NMR and its ability to influence circadian timekeeping in cellular reconstitution assays, we still don't understand exactly how the switch regulates circadian period.…”
Section: Discussionmentioning
confidence: 99%
“…Cyps are involved in a wide range of cellular processes, including protein folding, protein trafficking, and cell signaling (Naoumov, 2014). Despite the fact that all members of the PPIase superfamily share the same enzymatic activity, protein sequences and structures differ enormously between the three families (Barik, 2006;Davis et al, 2010;Hanes, 2015). The human genome is currently believed to encode 19 cyclophilins, 18 FKBPs, and three parvulins (Pin1, Par14, and Par17) (Gray et al, 2015).…”
Section: Cyclophilins and Cyclophilin Inhibitorsmentioning
confidence: 99%
“…Members of the PPIase protein family (e.g., cyclophilins, FKBPs, and parvulins) are enzymes found in both eukaryotes and prokaryotes, participate in cell signaling, gene transcription and assist folding and localization of proteins, respectively (Hanes, 2015). More recently, Cyps were shown to facilitate dissociation of the human Papillomavirus Type 16 L1 and L2 capsid proteins from L2/DNA complexes following virus entry (Bienkowska-Haba et al, 2012), while CypA was shown to bind Tomato bushy stunt tombusvirus and inhibit tombusvirus replicase assembly (Kovalev and Nagy, 2013).…”
Section: Introductionmentioning
confidence: 99%